Sustainable Retaining Structure Incorporating Recycled Concrete Aggregate - Nurly Gofar; Alfrendo Satyanaga (Indonesian Geotechnical Journal, 2022)
Recycled concrete aggregate, that are easily found from destruction waste materials, has been used in the construction industry as an alternative for coarse aggregate component in concrete or as backfilling material in retaining structure. This paper presents the results of study on the use of the recycled concrete aggregate in the design of a newly developed sustainable retaining wall i.e., Geobarrier system (GBS). The GBS system was developed based on capillary barrier to limit water infiltration into the backfill soil while vegetative cover is used as provisions of the sustainable construction concept. Two types of concrete aggregate are used as components of capillary barrier i.e., fine and coarse aggregate. Laboratory test result shows the recycled concrete has similar mechanical and hydraulic properties as the natural aggregate; thus, can be used as alternative material. Stability and deformation analyses were carried out for 4 m high wall with 70o inclination. Results indicate that the retaining wall meet the requirement of the code of practice according to Eurocode 7 in terms of Factor of safety. Deformation analysis shows that the maximum deformation was only 4.5 mm at the bottom of the GBS wall.